Reactivity of platelet‐activating and nonplatelet‐activating anti‐PF4/heparin antibodies in enzyme immunosorbent assays under different conditions. (17th May 2019) - Nguyen, Thi‐Huong; Wesche, Jan; Raschke, Ricarda; Strobel, Ulrike; Bui, Van‐Chien; Delcea, Mihaela; Greinacher, Andreas
Abstract: Essentials At low pH and low salt concentrations: Maximal conformational change of PF4 upon complexation with heparin occurs. Changing physicochemical conditions may become an approach to better discriminate the signal of platelet‐activating‐ and nonactivating PF4/H Abs in antigen tests. Background: Enzyme immunosorbent assays (EIA) are widely used to detect human antiplatelet factor 4/heparin antibodies (aPF4/H Abs) to rule out heparin‐induced thrombocytopenia. EIAs cannot differentiate between clinically relevant, platelet‐activating, and nonrelevant, nonplatelet‐activating Abs and only ~50% of patients' sera testing positive by EIA contain antibodies that activate platelets. Recently, we have shown platelet‐activating aPF4/H Abs bind more strongly to PF4/H complexes than nonplatelet‐activating antibodies. Antigen‐antibody interactions are known to depend on electrostatic interactions governed by pH, heat, and ionic strength. We tested whether changes in pH and ionic strength can improve the specificity of EIAs detecting aPF4/H Abs. Methods: We investigated first the conformational change of PF4 when binding to heparin under various pH and salt conditions using circular dichroism spectroscopy, and then the binding of aPF4/H Abs to PF4/H complexes by EIA. Results: Maximal conformational change of PF4 on complexation with heparin was identified at low pH and low salt concentrations. EIA tested with a large number of sera at 50 mmol/L NaCl, pH 6.0 shows a potential to increase the specificity for the detection of platelet‐activating aPF4/H Abs. Conclusion: Changing physicochemical conditions may become an approach to better discriminate the signal of platelet‐activating and nonactivating PF4/H Abs in antigen tests.